Encapsulation of flaxseed in a dolomitic limematrix: effects on feedlot performance and carcass characteristics of steers vs. heifers - Feltrin, G.; Alvarado-Gilis, Christian A.; Van Bibber-Krueger, Cadra L.; Klamfoth, D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
We have investigated the potential for using hydrated lime to form protective matrices with oil-rich feeds, such as flaxseed, to increase the incorporation of omega-3 fatty acids into meat. Dolomitic lime is mixed with ground flaxseed, water is added, the mixture is blended in a high-speed turbulizer, and the resulting material is then dried to form a granular matrix. During the manufacturing process, a portion of the hydrated lime becomes recarbonated. This recarbonated matrix is ruminally stable, which prevents rumen microbes from converting polyunsaturated oils to saturated fats. Additional recarbonation occurs in the rumen due to exposure to high concentrations of carbon dioxide produced by rumen microbes, further stabilizing the matrix. The objective of this study was to compare feedlot performance and carcass characteristics of heifers and steers fed traditional finishing diets to those of cattle supplemented with encapsulated blends of ground flaxseed and dolomitic lime hydrate.
Keywords: Beef; Omega-3 fatty acids; Rumen; Carcass traits